Model of Problem Based Instruction with Mind Mapping Method on Learning Outcomes of Grade 4 Elementary School Students: Model Problem Based Instruction dengan Metode Mind Mapping Terhadap Hasil Belajar Siswa Kelas 4 Sekolah Dasar - Cahyani, Lutfi Indah; Setiyawati, Enik (Universitas Muhammadiyah Sidoarjo, 2023)
This reserch is motivated by the low learning outcomes of elementary school students after hybride learning are a new problem in the world of education, so there is a need for a solution to improve student learning outcomes. The purpose of this study was to determine the influence and improvement of learning outcomes of grade IV students at SDN Sidoarjo on the material properties of light. The use of the PBI model with a mind mapping method on science material is one of the effective ways to help students to understand the concept of science, so that the learning carried out is based on authentic problems in real life. Trianto (2011) PBI is a model that uses problems in everyday life so that students understand concepts not by memorizing but through their own discoveries. This research uses quantitative research methods for true experimental design experiments. The results of the hypothesis test study using the Independent Sample T-Test t test obtained a sig (α) < 0.05 (0.002 < 0.05). The percentage of increase in n-gain in the experimental class was 58% and the control class was 36%, so it can be concluded that there is a significant influence on the use of problem-based instruction models with the mind mapping method on the learning outcomes of grade IV students elementary school.